Формирование свойств листовой двухслойной коррозионно-стойкой стали, полученной плакированием прокаткой - Загорянский, Олег Владимирович (НТУ "ХПИ", 2017)
Статья посвящена исследованию механических свойств двухслойного коррозионно-стойкого листового проката (на примере композиции сталей 09Г2С и 12Х18Н10Т), получаемого плакированием прокаткой. Технологические параметры процесса плакирования прокаткой принимались в соответствии с разработанной ранее моделью. Установлено, что максимальная прочность соединения слоев обеспечивается при относительной деформации в первом проходе плакирования прокаткой не менее 45%. Механические испытания образцов из полученных двухслойных листов определялись в соответствии с методикой испытаний, приведенной в ГОСТ 10885-85. Описана методика испытаний слоев на отрыв и приведены результаты испытаний. Результаты механических испытаний двухслойных листов показали, что значения механических свойств двухслойных листов значительно превышают минимальные регламентированные стандартом для данного вида проката.

The article is devoted to the investigation of the mechanical properties of a two-layer corrosion-resistant sheet metal (for example, the composition of steels 09Г2С and 12X18Н10T), obtained by cladding by rolling. The necessity of conducting theoretical and experimental invest igations of the process of obtaining a two-layer rolled metal is due to the continuous expansion of the sphere of its application, increasing requirements to its properties. On the base of analysis of the components of the corrosion-resistant two-layer bimetallic sheet to explore the regularities of properties formation of corrosion-resistant bimetal obtained using the method of cladding by rolling. As methodology were used the regularities of the formation and behavior of various phases in alloy steels, which influence the composition, properties and processing of steels. As findings of the paper we can consiner promising technologies for production and further processing of laminated metal composites are specific, the output parameters of the process depend on various factors associated with the application of considerable deforming forces and the use of high-energy treatment methods, therefore require further theoretical and experimental development. Originality (value) of the paper consists in investigating the regularities of formation of properties of corrosion-resistant bimetal obtained using the method of cladding by rolling.
Formation of the properties of sheet two-layer corrosion-resistant steel produced by cladding by rolling
Keywords: низколегированная сталь; повышенная прочность; плакирование прокаткой; двухслойная композиция; механические свойства; corrosion-resistant steel; low-alloy steel of high strength; cladding by rolling; two-layer composition; mechanical properties